Development of Mechatronics Trainers as Practical Learning Media for Electrical Engineering Vocational Education Students - Irwanto Irwanto; Ratna Ekawati (Jurnal Pembelajaran Fisika, 2021)
This study aims to produce a mechatronics trainer and job sheet product as a practical learning medium in mechatronics courses, as well as to determine the feasibility level of mechatronics trainer and job sheet products. The research method used is development research. The development used adopts the ADDIE model which consists of five stages, namely analyze, design, development, implementation, and evaluation. Data collection techniques used include interviews, observations, and questionnaires. Testing the feasibility level of the mechatronics trainer involving four media experts and four material experts, as well as users were carried out by students of the sixth semester of the 2018 electrical engineering vocational education study program. The data analysis technique used is descriptive qualitative and quantitative analysis. The results obtained for the media expert feasibility test score of 93.63 with a very decent category, for the material expert score, obtained 90.76 including the very feasible category, and the results obtained from users with a score of 88.76 so it can be stated that mechatronics trainers and job sheets can be used as media mechatronic practice learning in the electrical engineering vocational education study programKeywords: development, mechatronics, practice, media, learningDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202107